SOSIALISASI NILAI-NILAI AGAMA PADA ANAK DALAM KELUARGA DI DESA SEBELE KECAMATAN BELAT KABUPATEN KARIMUN - Dwi Asmara; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research was to know how the socialization in the family and what were the religion values that was socialize of the family in Sebele village of Belat subdistrict of Karimun regency. When was praying together and jumat prayer the number of childrens were little than the adult peoples or old peoples, the childrens always spoke filthy and unpolite to their friends and to adult.To know how the socialization in the family, what were the religion values that was socialize of the family in Sebele village of Belat subdistrict of Karimun regency, so the writer collected the data used interview guidence technique with respondences. The population of this research was the whole of the society that profess of Islam that had the childrens which attain the age of 7-13 years old. In this research, the writer used purposive technique sampling in taking the data, purposive technique sampling is taking the data based on certain creteria or certain judgment. The writer decided that 20 females and 20 childrens as the samples.The result of the research showed that religion values that socialize in family consisted of realization of praying, recite an Al-quran, Ramadhan fasting, the attitude to the parents include the polite attitude and the attitude to their friends were run well. It was suitable with the purpose, there were; planting the religion values to the childrens as a directive in implementation of Islam. If we seen from the percentage, the number of not quite in implementation of religion values was adequate good. This things based on the theories were influenced of how the socialization that accepted of childrens in family. The religion attitude of the childrens in family included realization of praying, recite an Al-quran, Ramadhan fasting, the attitude to the parents and attitude to the friends were adequate good. But, the childrens still did the violation of the religion values and religion norm, this happened because of the control of the parents was so weak.Key words: Socialization, Religion Values, Childrens’ attitude